HUBUNGAN USIA MENIKAH DENGAN KEJADIAN KANKER SERVIKS DI WILAYAH KABUPATEN BANTUL YOGYAKARTA - Suryati; Siti Nur Hidayah; Viantika Kusumasari (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Cervical cancer is a malignant tumor due to the growth of abnormal cells in the female reproductive system. The prevalence of cervical cancer is highest in DIY 4,86 per 1000 population. One of cause cervical cancer is infection of HPV virus that can be caused by age of marriage. Objetive: The purose of this study was to determine the relationship of the marriage age with the incidence of cervical cancer. Method: The method used in the research is case control study. Sampling technique is purposive sampling. This study used 76 samples, consisting of 38 case groups and 38 control groups. The data were analyzed by chi-squere test. Result: Most respondent at the case group first married at age < 20 years (57,9%) than at the control group the majority of the age of first marriage at age ≥20 years (78,9%). After testing with Chi-Squere analysis the result obtained (p=0,002; CI 1,875-14,177; OR=5,156) which means there is a significant relationship between age of marriage with cervical cancer in the region of Bantul Regency Yogyakarta. Conclution: Women married at < 20 years of age have a 5 times greater risk of cervical cancer than women married at age ≥ 20 years.